EFFECTIVE PEDAGOGICAL MECHANISMS FOR DEVELOPING PRACTICAL SKILLS IN TECHNOLOGY LESSONS - Madraximova Xalimaxon (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Annotation: This article examines effective pedagogical mechanisms aimed at developing practical skills in technology lessons. In the context of modern educational reforms, strengthening students’ practical competencies has become a primary goal of technology education. The study highlights various instructional strategies, including active learning methods, project-based tasks, problem-solving activities, and the integration of modern educational technologies. Emphasis is placed on the importance of creating a practice-oriented learning environment where students can actively engage in hands-on activities and apply theoretical knowledge in real situations. The role of the teacher as a facilitator and organizer of practical work is also discussed. The results indicate that the use of effective pedagogical mechanisms significantly improves students’ practical skills, motivation, and overall learning achievement.